Magic: A Modern Alleviating Constituent of Anxiety Levels in Children - CH Chandana Krishna Shree; Priya Nagar; HR Pooja; Andrea Natalia Mascarenhas (Journal of South Asian Association of Pediatric Dentistry)
Background: Anxiety in the dental setup is a most encountered problem associated with fear and stress, which has overemphasized its impact on the pediatric population. The lack of cooperativeness of children seen in the dental setup is mainly accredited to the behavioral expression of anxiety. There is a requirement for a constructive technique in dealing with children with obstinate attitudes. The magic technique is a new epoch in dentistry that can be used in strong-willed children. The magic technique helps in distracting the child and thus helps the child to relax and the dentist to perform the necessary treatment. Aim: To evaluate the change in behavioral attitude during the first visit in children and adolescents using magic distraction and audio-video distraction aids. Materials and methods: A total of 60 children of the age-group 4–13 years, who are recognized as strong-willed children, were chosen for the study. Children falling under the inclusion criteria were treated with endodontic and surgical procedures requiring local anesthesia administration and were assessed using three distraction aids (audio, audio-video, and magic group). Anxiety was assessed before and after the procedures using the Chotta Bheem and Chutki anxiety scale. Results: Mean anxiety levels were observed to be significantly reduced with the magic group using the thumb and light trick, followed by the audio-video group and then with the audio group. Conclusion: The use of distraction aids significantly reduced anxiety levels in children and adolescents.